Penerapan Model Pembelajaran Kooperatif Tipe STAD Dalam Meningkatkan Pemahaman Konsep Matematika Materi Himpunan Pada Siswa Kelas VII 4 SMP Negeri 13 Tahun 2016 - E. Ernawilis (Instructional Development Journal, 2018)
Background of this research is about the low interest in following the process of classroom learning spread by the author to 39 students in class VII 4 SMP Negeri 13 Pekanbaru. Learning that has been too monotonous adds to the cause of the low interest in learning which affects the poor results of learning, especially in learning mathematics. Therefore, there needs to be a new trobosan in order to increase students' learning interest in following the learning. This research was conducted in Pekanbaru City precisely on the students of class VII 4 SMP Negeri 13 Pekanbaru in the Lesson 2016. The purpose of this research is to know by using STAD type cooperative learning model can improve the understanding of basic concepts of mathematics discussion of the students of class VII 4 SMP Negeri 13 Pekanbaru Year 2016. This research consists of 2 cycles, while every cycle I is done in 4 meetings and on the second cycle conducted 2 meetings. Each cycle consists of steps Planning / preparation of action, implementation of action, observation and reflection. After the results of cycle 1 are obtained and have been reflected, further improvement is made to proceed to the next cycle if necessary. The result of this research is the increasing of the students ability to master the learning material that is marked with the value of cycle I, the number of students who reach KKM as many as 24 students or 72.73%, on the second cycle as many as 28 students or 87.5%. The conclusion of this class action research is in general could be happened saturation of student in follow lesson given by teacher so that need new breakthrough so that student become willing and interested in follow learning. By using STAD type cooperative learning method impact on result of research every cycle which increase significantly.